2021
DOI: 10.1007/jhep10(2021)028
|View full text |Cite
|
Sign up to set email alerts
|

Complexity from the reduced density matrix: a new diagnostic for chaos

Abstract: We investigate circuit complexity to characterize chaos in multiparticle quantum systems. In the process, we take a stride to analyze open quantum systems by using complexity. We propose a new diagnostic of quantum chaos from complexity based on the reduced density matrix by exploring different types of quantum circuits. Through explicit calculations on a toy model of two coupled harmonic oscillators, where one or both of the oscillators are inverted, we demonstrate that the evolution of complexity is a possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…• Recently in [123][124][125] Circuit Complexity has been explored in continuous variable system and open quantum systems, similarly techniques and analysis can be done with study of Circuit Complexity in context of cosmological perturbations.…”
Section: Future Prospectsmentioning
confidence: 99%
“…• Recently in [123][124][125] Circuit Complexity has been explored in continuous variable system and open quantum systems, similarly techniques and analysis can be done with study of Circuit Complexity in context of cosmological perturbations.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Once again we have denoted the extra copy of H as H anc to distinguish it from the original. In that sense, this process of operator-state mapping is a special case of the purification discussed above [49]. The most important difference is that the state |O in (2) associated to the operator Ô is unique, there are no free parameters introduced in the mapping.…”
Section: Complexity For a Density Matrixmentioning
confidence: 99%
“…In this section, we will investigate the circuit complexity for our open quantum system by applying operator-state mapping [49]. Considering explicitly the system's density matrix (Eq.…”
Section: Complexity By Operator-state Mappingmentioning
confidence: 99%

Complexity for Open Quantum System

Bhattacharyya,
Hanif,
Haque
et al. 2021
Preprint
Self Cite
“…One of the most striking questions is whether it is possible to use quantum information tools to describe quantum chaos [12][13][14][15][16][17][18], such as circuit complexity [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Recent works have shown that circuit complexity can indeed detect quantum chaos [35][36][37]. In particular, it was found that chaotic behavior can be characterized by the complexity of bidirectional evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the complexity here increases linearly with time and hence has no upper bound. However, the complexity calculated by different methods in Ref [37]. has an upper bound.…”
mentioning
confidence: 99%